Answer:
Σmf = 23347
Σm²f = 1621631
(Σmf)² = 545082409
Step-by-step explanation:
The symbol Σ means that we need to sum all the products of m and f.
So, Σmf is equal to:
Σmf =76(94) + 37(92) + 27(63) + 98(62) + 62(81)
Σmf = 7144 + 3404 + 1701 + 6076 + 5022
Σmf = 23347
Then, to find Σm²f, we need to find the square of m, so:
Σm²f = (76)²(94) + (37)²(92) + (27)²(63) + (98)²(62) + (62)²(81)
Σm²f = 5776(94) + 1360(92) + 729(63) + 9604(62) + 3844(81)
Σm²f = 542944 + 125948 + 45927 + 595448 + 311364
Σm²f = 1621631
Finally, (Σmf)² is equal to:
(Σmf)² = (23347)²
(Σmf)² = 545082409
Therefore, the answers are:
Σmf = 23347
Σm²f = 1621631
(Σmf)² = 545082409